PEMBENTUKKAN KARAKTER BERBASIS AJARAN TAMANSISWA PADA PEMBELAJARAN IPS PESERTA DIDIK KELAS V DI SD NEGERI BALI LUHUR KECAMATAN BUAY MADANG TIMUR - Wayan Deni Saputra; Yuyun Yulia; Heri Maria Zulfiati (Universitas Sarjanawiyata Tamansiswa, 2023)
The research objectives include: 1) To describe the character formation of students through Social Studies class V at SD Negeri Bali Luhur, 2) To describe challenges and solutions for teachers in Social Studies learning for the character building of Class V students at SD Negeri Bali Luhur, 3) To describe efforts made to overcome obstacles in the implementation of Social Studies class V at SD Negeri Bali Luhur. This type of research is using descriptive qualitative research, which uses interview, observation, and documentation techniques. In this study, researchers will explore and find out whether the character building of students through social studies learning has been implemented or not. This research was conducted at Bali Luhur Public Elementary School, East Buay Madang District. The analysis used is the analysis of the Miles and Huberman models. Researchers reduce, present, draw conclusions, and verify data. Based on the results of data analysis, the conclusions are obtained: 1. The teacher carries out learning through 3 stages, namely introduction, core, and closing. At these 3 stages of learning the teacher forms the character of students through activities carried out by students with group discussions. Social studies learning can shape the character of students to be more sensitive to social problems that exist in everyday life, for example loving each other, living in harmony, then teaching students to learn how to tolerate each other, respect each other, trust each other, and mutual cooperation. 2) There is still limited time, there are still some who have not implemented or applied the character values ​​that have been taught by teachers at school, other factors are still limited facilities and infrastructure. The supporting factors are the existence of exemplary and guiding awareness from the teacher, the content of character education in learning tools (RPP), the existence of motivation, good coordination from all parties in the school, the cooperation of each component of the school in shaping the character of students with higher commitment. 3) Providing motivation to students, inviting students to play games in the middle of the learning process, other efforts the teacher makes to approach students, provide feedback and relate it to everyday life, and choose appropriate learning methods.